EFEMP1 as a Potential Biomarker for Diagnosis and Prognosis of Osteosarcoma - Wang, Zhuo (Biomed Res Int, 2020)
Osteosarcoma (OS) is the most common primary bone malignancy. Our previous study revealed an association between the level of epidermal growth factor-containing fibulin-like extracellular matrix protein 1 (EFEMP1) and the invasion, metastasis, and poor prognosis of OS. However, the exact correlation between the serum EFEMP1 level and OS diagnosis and progression was unclear. This study is aimed at determining the value of the serum EFEMP1 level in the diagnosis and prognosis of OS. Fifty-one consecutive OS patients were prospectively registered in this study. The serum EFEMP1 levels were measured using ELISA at diagnosis, after neoadjuvant chemotherapy, and before and after surgical treatment. Sixty-nine healthy subjects in the control group, nine patients with chondrosarcoma, and 12 patients with giant cell tumor of the bone were also enrolled in this study. Surgical orthotopic implantation was used to generate a mouse OS model, and the correlation between the circulating EFEMP1 levels and tumor progression was examined. Then, OS patients had significantly higher mean serum EFEMP1 levels (7.61 ng/ml) than the control subjects (1.47 ng/ml). The serum EFEMP1 levels were correlated with the Enneking staging system (r = 0.32, P = 0.021) and lung metastasis (r = 0.50, P < 0.001). There was also a correlation between the serum EFEMP1 level and EFEMP1 expression in the respective OS samples (r = 0.49, P < 0.001). Additionally, patients with either chondrosarcoma or giant cell tumor of the bone had significantly higher serum EFEMP1 levels than OS patients. Surgical and chemotherapeutic treatment led to an increase in the serum EFEMP1 levels. Then, the destruction of bone tissues might be one of the factors about the EFEMP1 levels. In the mouse OS model, the serum EFEMP1 level was correlated with tumor progression. Our results suggested that serum EFEMP1 levels might be used to distinguish OS patients from healthy controls and as an indicator for OS lung metastasis. Serum EFEMP1 levels could serve as a new and assisted biomarker for the auxiliary diagnosis and prognosis of OS.